Transcription of reference genes used for quantitative RT-PCR in Atlantic salmon is affected by viral infection - Jørgensen, Jorunn B; Løvoll, Marie Therese; Austbø, Lars; Rimstad, Espen; Frost, Petter (Veterinary Research, 2011)
Relative quantification using RT-qPCR is a widely used method for transcription profiling. Transcript levels of target genes in fish after experimental infection is often reported without documentation of stably transcribed reference genes. We present results demonstrating that transcription of typically used reference genes in Atlantic salmon is not stable during experimental infection with salmon pancreas disease virus (SPDV). Transcript levels 0 to 6 weeks after challenge revealed statistically significant changes between time-points that corresponded with a peak in viral load 3 weeks after challenge. The results emphasize the need for thorough method validation prior to transcriptional studies during viral infections.